A k-Dimensional System of Fractional Finite Difference Equations - Dumitru Baleanu; Shahram Rezapour; Saeid Salehi (Abstract and Applied Analysis)
We investigate the existence of solutions for a k-dimensional system of fractional finite difference equations by using the Kranoselskii’s fixed point theorem. We present an example in order to illustrate our results.